PENGAWASAN PELAKSANAAN PROTOKOL KESEHATAN OLEH SATUAN POLISI PAMONG PRAJA DI KABUPATEN JAYAPURA PROVINSI PAPUA - Salama, Timoty Yusuf; Manuri, Mercy Christa (Jurnal Konstituen, 2022)
The spread of COVID-19 occurred quickly to almost all corners of the world including Indonesia. The increasing number of positive cases prompted the government to issue several regional regulations regarding health protocol discipline as an effort to prevent and control Covid-19, in this case the Civil Service Police Unit has the task of overseeing health protocols. The problem encountered in this research is the increasing cases of Covid-19 in Jayapura Regency from being positive, being treated to death so it is necessary for this research to be conducted to find out how the supervision of the implementation of the Health Protocol is carried out by the civil service police unit of Jayapura Regency, the inhibiting factors and efforts in dealing with it. This study uses the theory of Supervision which is Robbin and Coulter in Satriadi (2016). The research method in this study used a qualitative descriptive method by providing an overview of facts and data that occurred in the field through data collection techniques, namely observation, interviews and documentation. Data collection techniques are interviews, documentation, observation. The data analysis technique used is an interactive model by means of data reduction, data presentation, and drawing conclusions. The results of the study show that the Civil Service Police Unit is an important key to overseeing the CovId-19 Health Protocol in Jayapura Regency and has carried out its duties well seen from the declining number of Covid-19 in Jayapura district. There are several obstacles in carrying out their duties both from internal factors and external factors. The efforts made by the Civil Service Police Unit in supervising the implementation of the Covid-19 health protocol in Jayapura Regency are conducting further socialization and suppressing hoax news that is spreading and imposing sanctions in accordance with the applicable Regent Regulations.